2020
DOI: 10.1021/acs.langmuir.0c00087
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Characterization of Oleanolic Acid–Human Serum Albumin Complexes for Pharmaceutical and Biosensing Applications

Abstract: Among numerous compounds found in marine organisms, triterpenes have attracted considerable research interest due to a beneficial impact on health including anti-inflammatory, antitumor, antiviral, and antioxidation effects. Specifically, new functionalities of oleanolic acid (OLA) have been revealed recently, indicating possible applications in nutrition and pharmaceuticals. However, this bioactive material has limited value due to low water solubility and stability. Therefore, oleanolic acid needs a carrier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…The thermodynamic analysis showed that the basic forces acting between bovine serum albumin and the triterpene were hydrogen bonds, van der Waals forces and hydrophobic interactions [ 85 ]. Dopierala et al [ 86 ] found that the binding of OA to albumin can be irreversible according to pH, ionic strength and temperature, which may have a significant impact on the distribution of oleanolic acid in the human body. Peng et al [ 85 ], Bhattacharya et al [ 87 ] and Subramanyam et al [ 88 ] anticipated that the complexation of plant triterpenoids with protein might be exploited as a biologically relevant model for evaluating the physiologically applicable no-covalent complexes in the in vivo examination of triterpenoid properties such as accumulation, bioavailability and distribution.…”
Section: Biological Activity Of Oamentioning
confidence: 99%
“…The thermodynamic analysis showed that the basic forces acting between bovine serum albumin and the triterpene were hydrogen bonds, van der Waals forces and hydrophobic interactions [ 85 ]. Dopierala et al [ 86 ] found that the binding of OA to albumin can be irreversible according to pH, ionic strength and temperature, which may have a significant impact on the distribution of oleanolic acid in the human body. Peng et al [ 85 ], Bhattacharya et al [ 87 ] and Subramanyam et al [ 88 ] anticipated that the complexation of plant triterpenoids with protein might be exploited as a biologically relevant model for evaluating the physiologically applicable no-covalent complexes in the in vivo examination of triterpenoid properties such as accumulation, bioavailability and distribution.…”
Section: Biological Activity Of Oamentioning
confidence: 99%
“…Several publications have appeared recently documenting LB films built of gold nanoparticles, zinc oxide, , magnetic nanoparticles and nanowires, , fullerenes, graphene, and graphene oxide. , Ariga introduced the concept of nanoarchitectonics, which uses a liquid interface to form controlled nanostructures for nanosensing, nanophotonics, and molecular electronics . In addition, much research on complex, multicomponent monolayers has been done including thermodynamic characterization, rheological studies, and deposition on various substrates. For instance, various biomolecules can be incorporated into the lipid monolayer such as proteins, , chitosan, collagen, and keratin as well as xenobiotics, , extending the applications of Langmuir films in the biomedical field.…”
Section: Introductionmentioning
confidence: 99%
“…Monolayers are formed at the air–water interface, which allows for the acquisition of a lot of information about the interactions and the physicochemical properties of its components. To obtain stable lipid monolayers that simulate biological model membranes, the Langmuir method can be used, which is a good technique to study the structures and properties of lipids, proteins and surfactants [ 16 , 17 , 18 ]. Furthermore, the properties of model lipid monolayers are similar to those of real biological membranes [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%